2011
DOI: 10.4161/cc.10.24.18663
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing is impaired in ATM-defective cells

Abstract: The transcription factor hypoxia-inducible factor 1α (HIF-1α) is a master regulator of cell adaptation to decreasing oxygen levels. High oxygen tension promotes proteosomal degradation of HIF-1α via a pathway that requires hydroxylation of prolines 402 and 564. Low oxygen tension, hypoxia, inactivates the hydroxylases responsible for these modifications through a mechanism that is not fully understood but appears to require mitochondrial respiration and production of reactive oxygen species, ROS. Cells from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Hypoxia and HIF-1␣ may also affect directly the activity of the ataxia telangiectasia mutated (ATM) pathway, which plays a critical role in DNA repair in HSCs during aging 33 or after ionizing radiation. [34][35] Indeed, HIF-1␣ is rapidly degraded even in hypoxic conditions in cells with defective ATM kinase, 36 suggesting that ATM is another critical regulator of HIF-1␣ protein stability. Reciprocally, hypoxia activates ATM protein kinase by DNA damage-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and HIF-1␣ may also affect directly the activity of the ataxia telangiectasia mutated (ATM) pathway, which plays a critical role in DNA repair in HSCs during aging 33 or after ionizing radiation. [34][35] Indeed, HIF-1␣ is rapidly degraded even in hypoxic conditions in cells with defective ATM kinase, 36 suggesting that ATM is another critical regulator of HIF-1␣ protein stability. Reciprocally, hypoxia activates ATM protein kinase by DNA damage-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using Atm −/− mice, the authors demonstrated that the absence of ATM increased the levels of ROS in vivo and caused signs of oxidative stress in the central nervous system, in particular in cells of the cerebellum, the primary site of neurodegeneration in AT patients [81]. More recently, regulation of oxidative stress by ATM has been proposed to play a role in several cellular functions including haematopoietic and neuronal stem cell self-renewal and survival [8284], RTK activation [85] and hypoxia [86,87], that are often aberrantly regulated in cancer.…”
Section: Atm Dependent Modulation Of Signaling Pathways Outside Ddr Imentioning
confidence: 99%
“…Evidence for a link between ATM and hypoxia has been provided by several laboratories [86,87,9598]. Importantly, hypoxia has been shown to trigger ATM activation which in turn phosphorylates HIF-1α, a transcription factor that plays a central role in the cellular response to hypoxia, by activating the downstream regulation of metabolism, mitochondrial function and angiogenesis [86].…”
Section: Atm Dependent Modulation Of Signaling Pathways Outside Ddr Imentioning
confidence: 99%
“…The pcDNA3-HER2 construct was kindly provided by P. Nisticò and the shATM construct by Y. Lerenthal and Y. Shiloh 42 . Control shRNA, siR5, has been described 43 .…”
Section: Methodsmentioning
confidence: 99%